Review Penerapan Konsep Kota Hijau Pada Perumahan Klaster - Yosi Bruina Waspodo; Muhammar Khamdevi (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2019)
This study discusses the analysis of the application of the concept of green city in cluster dwellings in Gading Serpong. The selected case studies are Desa Menteng and Grand Amarillo. The selection of case study objects is based on awards obtained from property awards. This study tries to uncover the theory of the concept of a green city that is now used by P2KH (Green City Organizers' Alloy). Assessment uses indicators determined by P2KH Licenses; Green City Planning and Design, Green Open Space Planning, Efficient Energy Consumption (Green Energy), Effective Water Management (Green Water), Environmentally Friendly Waste Management (Green Waste), Green Buildings, Sustainable Transportation System Implementation (Transportation Green), Increasing the Role of Communities as Green Communities. The method used in this research is descriptive qualitative method. The final results found by one cluster according to the specified criteria are not yet clustered.